CT-guided microwave ablation of renal cell carcinoma in a horseshoe kidney - Vellia Zhou, BS; Wenhui Zhou, MD, PhD; Sanna E. Herwald, MD, PhD; Ronald S. Arellano, MD (Radiology Case Reports)
Renal fusion anomalies are rare congenital malformations that comprise horseshoe kidney and crossed fused ectopia. Renal tumors arising from these fusion anomalies are anatomically complex, and surgical management can be technically challenging because of altered renal anatomy. Percutaneous CT-guided ablation can overcome some of these anatomical constraints, and microwave ablation has the additional benefit of shorter treatment time and reduced sensitivity to heat sink effects compared to other ablative modalities. The present report describes the successful use of microwave ablation to treat renal cell carcinoma arising in a horseshoe kidney with no local recurrence after 4.5 years, demonstrating the feasibility of MWA in managing RCC in anatomically complex locations.